SEBARAN DAERAH PENANGKAPAN IKAN PADA PERIKANAN SKALA KECIL DI KABUPATEN PANGANDARAN, JAWA BARAT: Fishing Ground Distribution of Artisanal Fisheries in Pangandaran Regency of West Java - Prayitno, Muhamad Riyono Edi; Rahman, Abdul; Hakim, Muhammad Romdonul (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
Capture fisheries in Pangandaran Regency, West Java are dominated by small-scale fishers. As many as 98% of fishing vessels in Pangandaran are under 5 GT. The small fishing vessels restrict Pangandaran fishers from operating further outside the Pangandaran Bay. As a result, the fishing pressure around the bay increases. This study aims to analyze the fishing grounds distribution of Pangandaran fishers. The selection of fishing locations was carried out using the participatory mapping method by asking fishers to show the fishing location on the map provided. A total of 163 respondents from 4 different fish landing bases were interviewed to obtain data on fishing positions and dominant caught fish. The results showed that the fishing grounds of Pangandaran Regency fishers are divided into Pangandaran Bay (east coast) and Parigi Bay (west coast) with the highest concentration of fishing grounds in the western part of both bays. Fishers choose this location because it is safer from waves and blocks the target fish that migrate from west to east. There were 25 species of fish caught by Pangandaran fishers, but only 13 species were dominant with Trichiurus savala and Pampus argenteus being at the top. The results of this study are expected to be the basis information for determining policies to develop the fishing capacity of coastal fisheries in Pangandaran to offshore, hence it can reduce fishing pressure in the coastal waters. Keywords: fishing ground, artisanal fisheries.